Islamic thought in the dialogue of cultures : a historical and bibliographical survey - Daiber, Hans, 1942- (Themes in Islamic studies, 2012)
The monograph aims at a historical and bibliographical survey of the qur??nic and rational world-view of early Islam, of the period of translations from Greek into Syriac and Arabic, and of the impact of Islamic thought on Europe.